Islamic Financial Education as a Preventive Instrument in Mitigating Riba-Based Credit Transactions: An Empirical Study - Darmawan Dwi Prasetyo; M Arif Musthofa; Wargo; Daud (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to examine the effect of literacy on community decision-making in engaging in credit-based buying and selling transactions containing elements of riba in Geragai District, Tanjung Jabung Timur. The research focuses on members of the local community as its primary subjects. A quantitative approach was employed using a simple random sampling technique, resulting in a total of 50 respondents. Data were analyzed using a t-test and simple linear regression with the assistance of Microsoft Excel. The findings reveal that literacy has a positive and statistically significant influence on community decisions to engage in credit transactions involving riba. This indicates that higher levels of literacy are associated with more informed and rational decision-making regarding such financial practices. The study highlights the importance of improving literacy particularly in the context of financial and Islamic perspectives to guide communities toward more appropriate economic behavior